Strategic Diversification : A Case of a National Bank - Mainrai, Girish (Prabandhan: Indian Journal of Management, 2017)
Profit is essential for survival of any organization, which depends on a number of sector-specific factors. The present case related to National Bank, which felt the impact on profitability, on account of over dependence on corporate sector for its business. Alarmed with diminishing profitability, the bank undertook a slew of measures under â€œProject Akashâ€ for increasing retail credit. These measures included establishing specialized retail centres and marketing setup for processing of retail loans, tie-ups with auto dealers, builders, and educational institutes along with promotion campaigns. The project did not deliver the results as anticipated by the management of the bank. When the management got into the nitty gritty of affairs, it realized that the project launched with a single objective had many ramifications, which needed to be probed further. These included customer service, human resources, marketing setup, operations, and many others. The management of the bank resolved to make the project successful.